Interplaying anions in a supramolecular metallohydrogel to form metal organic frameworks - Karak, Suvendu; Kumar, Sushil; Bera, Saibal; Diaz Diaz, David; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
The remarkable effect of anions on the transition from supramolecular gels to crystalline phases has been described. An amino acid-based metallohydrogel was transformed into different metal-organic frameworks through the selective picking of anions. The metallohydrogel and the resulting metal-organic frameworks (MOFs) were thoroughly characterized. The results demonstrated controlled access over the binding of a particular anion to selectively form a particular MOF.